Pengaruh Kualitas Layanan Customer Service Terhadap Kepuasan Nasabah Pada Bank Rakyat Indonesia Cabang Kayuagung - Intan Sila; Purwati Purwati; M. Syahirman Yusi (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This study analyzes customer satisfaction at PT Bank Rakyat Indonesia (Persero) Tbk. Kayuagung Branch. The independent variable in this study is the variable of customer service quality which consists of 5 dimensions, namely physical evidence, reliability, assurance and certainty, and empathy, while the dependent variable in this study is customer satisfaction. The sample in this study amounted to 100 customers using a sampling technique, namely incidental sampling. The analysis technique uses multiple linear regression analysis, the coefficient of determination test, the F test and the t test. This study found that the independent variables simultaneously have a significant effect on customer satisfaction. Partially it shows that the variables of physical evidence and assurance and certainty have a significant effect, while reliability, responsiveness and empathy do not have a significant effect on customer satisfaction